Implementasi Pengiriman Data Secara Nirkabel pada Palang Pintu Sungai untuk Mitigasi Bencana Banjir berbasis nRF24L01 - Yusriansyah Shohibul Hamzah; Mochammad Hannats Hanafi Ichsan; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Flooding is still a difficult problem to solve, especially in big cities, especially during the rainy season. At the peak of the rain with high rainfall, the river is difficult to fill the large water discharge. For development of river water flow that has more water discharge, sluice gates are used to build the discharge in the river flow. By using a doorstop that is connected wirelessly to minimize flooding, so that the air can be controlled with the communication system between the latches properly. The mechanism used is to send sensor data to Arduino mega2560 as a microcontroller with nRF2L01 as the sender, using fuzzy logic to determine the latch opening of the river floodgates, and Simple Additive Weighting to see rainfall and received by Arduino nano which has nrf24l01 as a receipients where the average error percentage is 0,12%. The results obtained for calculating the rain sensor module when tested are in accordance with the conditions and output. And for the water level there is a sensor difference of 0.1375%.